Transition‐Metal‐Doped α‐MnO2 Nanorods as Bifunctional Catalysts for Efficient Oxygen Reduction and Evolution Reactions. Issue 9 (5th March 2018) - Lübke, Mechthild; Sumboja, Afriyanti; McCafferty, Liam; Armer, Ceilidh F.; Handoko, Albertus D.; Du, Yonghua; McColl, Kit; Cora, Furio; Brett, Dan; Liu, Zhaolin; Darr, Jawwad A.
Abstract: Nano‐sized α‐MnO2 nanorods doped with Co or Ru were directly synthesized using a continuous hydrothermal synthesis process (production rate 10 g h −1 ) and investigated as relatively inexpensive (due to the small Ru content) bifunctional catalysts for both the Oxygen Reduction Reaction (ORR) and Oxygen Evolution Reaction (OER). The materials were extensively characterized using a range of analytical methods; these including Extended X‐Ray Absorption Fine Structure (EXAFS) spectroscopy measurements, which was accompanied by density functional theory studies, in order to elucidate the role of dopants in α‐MnO2 structure. Electrochemical ORR and OER investigations of the as‐prepared doped α‐MnO2 nanomaterials were compared to more expensive Pt/C or RuO2 catalysts. The doped manganese oxide nanomaterials were used as bifunctional catalysts in the positive electrode of zinc air batteries (with oversized zinc metal negative electrode and limited density of discharge window) and displayed excellent performance (the overpotential was 0.77 and 0.68 V for α‐MnO2 modified with 7.6 at% Co and 9.4 at% Ru, respectively). Overall, as a result of doping, this study achieved improved bifunctional catalytic activities of metal oxide catalysts, which was comparable to more expensive alternatives. Abstract : Bifunctional catalysts: α‐MnO2 can be synthesized via a scalable hydrothermal synthesis process. Modification of α‐MnO2 with Co and Ru atoms improves the OER catalytic performance. This can help to improve the energy efficiency of zinc air batteries.